Effectiveness of a self-management mobile app on the quality of life of women with breast cancer: a study in a developing country - Zahra Mohammadzadeh; Samereh Eghtedar; Haleh Ayatollahi; Mohamad Jebraeily (BMC, 2022)
Abstract Background Self-management involves taking responsibility for personal health and taking the initiative to do so. This can be accomplished by learning information and skills that will help consider the difficulties may encounter during and after cancer treatment. With this perspective, we have aimed to develop a self-management mobile app for women with breast cancer in Iran and evaluate its impact on the quality of life of patients. Method This study is a methodological study in 2021. We developed the app during three phases. The first phase aimed at identifying educational content and designing user experience, the second phase aimed at developing and implementing the app, and the third phase aimed at evaluating pre-and post-implementation. Result In this study, an Android app for self-management women with breast cancer was developed. According to the results of the pre-and post-implementations among the most significant changes were in the quality of life level, highest respectively: social avoidance (Pre: 6.41-Post: 3.56), negative feelings (Pre: 5.93 - Post: 3.40), sexual function (Pre: 6.80 - Post: 5.04), sexual interest (Pre: 6.41 - Post: 4.75) and pain (Pre: 6.37 - Post: 4.97). And least the changes respectively: distress-family (Pre: 7 - Post: 7), distress-recurrence (Pre: 4.49 - Post: 4.38), benefits (Pre: 2.47 - Post: 3.12), appearance (Pre: 4.10 - Post: 3.32). Also, we calculated the usability evaluation of this app with the system usability scale (SUS); the overall rating score was 83/100, an excellent level (> 80.3), and a grade A. Conclusion The study shows that a breast cancer self-management app can support and improve the quality of life of women with breast cancer. We conducted this study to show that by developing a self-management app, women with breast cancer can improve their quality of life, − by increasing their self-management skills.